Gender and practice : knowledge, policy, organizations - Segal, Marcia Texler; Kelly, Kristy; Demos, Vasilikie (Advances in gender research ;, 2019)
This book contains an Open Access Chapter In 1995, the Fourth World Conference on Women: Action for Equality, Development and Peace affirmed the need to address gender inequalities and foster gender integration. Ever since, the field of gender professionals has been growing, yet the experiences, insights and data gathered have not been systematically examined and incorporated into an accessible body of knowledge. Working to address this, expert contributors demonstrate the depth and breadth of gender and practice. Including examples from Brazil, Cameroon, Ecuador, Nigeria, Sao Tome and Principe, the USA, and Vietnam, as well as chapters that take a global perspective, the research here looks at issues and activities relating to infusing gender in knowledge management, training, and practice. Including subjects such as education, agricultural production, and tourism, this volume offers a variety of perspectives that will appeal to any researcher in gender. Throughout the volume, expert practitioners situate their real-world experiences in the broader intersectional framework employed by their academic colleagues, offering policy makers, students, scholars, practitioners, and activists concrete examples of how and why gender is central to development.